2012
DOI: 10.3904/kjim.2012.27.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Inhibitor Improves Renal Tubulointerstitial Hypoxia of the Diabetic Rat Kidney

Abstract: Background/AimsRenal hypoxia is involved in the pathogenesis of diabetic nephropathy. Pentoxifyllin (PTX), a nonselective phosphodiesterase inhibitor, is used to attenuate peripheral vascular diseases. To determine whether PTX can improve renal hypoxia, we investigated its effect in the streptozocin (STZ)-induced diabetic kidney.MethodsPTX (40 mg/kg, PO) was administered to STZ-induced diabetic rats for 8 weeks. To determine tissue hypoxia, we examined hypoxic inducible factor-1α (HIF-1α), heme oxygenase-1 (HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Our study showed urinary protein excretion of the rats was significantly decreased after PTX treatment and the effect of higher dose of PTX was better than that of low-dose PTX or benazepril. These findings were consistent with those reported in the previous studies [3, [14][15][16][17] . With pathological methods, we proved that PTX was able to alleviate renal tissue damages of DN rats.…”
Section: Discussionsupporting
confidence: 95%
“…Our study showed urinary protein excretion of the rats was significantly decreased after PTX treatment and the effect of higher dose of PTX was better than that of low-dose PTX or benazepril. These findings were consistent with those reported in the previous studies [3, [14][15][16][17] . With pathological methods, we proved that PTX was able to alleviate renal tissue damages of DN rats.…”
Section: Discussionsupporting
confidence: 95%
“…35 Similarly, in another study, a decrease in HIF-1a and VEGF expression in the kidney of diabetic rats was shown. 36 However, the effect of PTX on NOS has not been investigated in the diabetic kidney so far. In the present study, we demonstrated that PTX ameliorated eNOS, iNOS and nNOS protein levels, but did not affect mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…32 There is a strong biologic rationale for inflammation, oxidative stress, and fibrosis, to be critical risk factors for renal disease progression in DKD. [33][34][35] Experimental research has shown that PTF diminishes renal tissue damage through beneficial anti-inflammatory, antioxidant, and antifibrotic effects, 17,36,37 resulting in attenuation of kidney disease progression. This outcome is maximized after combination with RAS blockers.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were white, with a mean age of 69.869.2 years, a similar distribution by sex (53.8% men and 46.2% women), and a mean duration of diabetes of 1563.4 years. The mean baseline eGFR was 37 (Figure 2). Likewise, glycemic control did not differ between groups during follow-up.…”
mentioning
confidence: 99%